Skeletal, dentoalveolar, and buccal bone changes using hybrid and tooth-borne expanders for RME and SARME in different growth stages - Kayalar Emre; Fıratli Sonmez; Darendeliler M. Ali; Dalci Kerem; Dalci Oyku (Sciendo, 2022)
To compare the skeletal, dentoalveolar and buccal bone thickness of tooth-bone-borne (Hybrid-H) and tooth-borne (TB) maxillary expanders used for rapid maxillary expansion (RME) in early and late adolescents and for surgically-assisted RME (SARME) in young adults.